DEDIAVER Sebagai Aplikasi Alternatif Tes Denver II untuk Tes Deteksi Dini Perkembangan Anak - Yulia Ery Kurniawati; Yulius Denny Prabowo (Jurnal Kajian Ilmiah, 2022)
One of the focuses of research and innovation in Indonesia is to encourage the development of health resilience and independence, and one of the concerns is child development. According to the Indonesian Pediatrician Association (IDAI), about 5-10% of children are estimated to have developmental delays and around 1-3% under the age of 5 years experience general developmental delays. Early Detection of Child Development Based on the Denver II Test (DEDIAVER) is a decision support system (DSS) application that can be used to detect child development using the Denver II Test instruments. This research aims to evaluate the DEDIAVER application and assess the feasibility of the DEDIAVER application as an alternative application for the Denver II Test for early detection tests of child development. The test is carried out by matching the results of the Denver II Test, which is carried out manually, with the results of the DEDIAVER application. As a result, for the test for children aged 0-2 years, the total accuracy for each developmental sector and age is 90.67%, while the test for children aged 2-6 years has an accuracy of 36%. The accuracy of the test for ages 2-6 years is only 36% due to the difference in the application's age calculation, which is 4-6 months older than the actual age. The age difference causes the questions for children over their age to be questioned.